Distinct PKA Signaling in Cytosolic and Mitochondrial Compartments in Electrically Paced Atrial Myocytes - Noa Kirschner Peretz; Sofia Segal; Ido Weiser-Bitoun; Yael Yaniv (Cells, 2022)
Protein kinase A (PKA) is a key nodal signaling molecule that regulates a wide range of cellular functions in the cytosol and mitochondria. The distribution of A-kinase anchoring proteins that tether PKA, the local interaction with degradation molecules, and regulation by Ca2+, may lead to distinct spatiotemporal cAMP/PKA signaling in these compartments. In this work, FRET-based sensors were used to investigate PKA signaling in the cytosol, outer mitochondrial membrane (OMM), and mitochondrial matrix (MM) and its crosstalk with Ca2+ in response to electrical stimulation of cultured rabbit atrial cells. A gradual decrease in PKA activity eliminating the ability of the atrial cells to respond to physiological electrical stimulation, was observed upon treatment of cells with H-89. Chelation of intracellular Ca2+ by BAPTA reduced PKA activity and diminished its response to forskolin, an AC stimulator. Under basal conditions, PKA activity in response to forskolin was lower in the OMM compared to the cytosol and MM. In response to electrical stimulation in the presence of ISO, distinct compartmentalization of PKA activity was observed, with higher activity in the cytosol and MM than in the OMM. Thus, distinct Ca2+-dependent spatiotemporal cAMP/PKA signaling exists in atrial cells, likely mediating its excitation and mitochondrial function.